Single kenaf fibre properties via in situ monitoring using acoustic emission - Anuar, Hazleen; Ahmad, Zuraida; Halim, Zahurin (2010)
Kenaf fibre reinforced polylactic acid biocomposites is a new material developed mainly due to the fact that it is environmentally friendly and alternative to the petroleum-based food packaging. Hence, it is important to determine mechanical properties of kenaf fibre for structural and physical applications. In this study, tensile properties and fracture behaviours of single kenaf fiber is tested via in situ monitoring with non-destructive acoustic emission (AE). During tensile loading, acoustic signal recorded higher amplitude above 20 dB up to the maximum force which corresponding to breakage of single kenaf fibre.